THE INFLUENCE OF AUTHORITATION LEADERSHIP, LOYALTY AND TRAINING ON EMPLOYEE PERFORMANCE: (Study on Restaurant Mie Aceh Titi Bobrok) - Natasya, Siti; Harahap, Kartini (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
In the realm of organizational management, leadership styles play a crucial role in shaping employee performance and outcomes. One such leadership style is the autocratic approach, characterized by centralized decision-making and hierarchical control. Loyalty and training also emerge as significant factors contributing to an employee's overall performance. Loyalty fosters a sense of commitment and dedication to the organization, while training enhances skills and knowledge, ultimately impacting employee effectiveness. This study aims to investigate the impact of autocratic leadership style, loyalty, and training, both partially and simultaneously, on employee performance at Titi Bobrok Aceh Noodle Restaurant. Using quantitative research, it explores relationships among these factors within a sample of 32 respondents, employing primary and secondary data analysis. The methodology encompasses validity tests, multiple linear analysis, and determination tests, revealing autocratic leadership's positive but insignificant effect, and loyalty and training's significant impacts on performance. Together, these factors notably influence performance, reflected by an R value of 0.938 and 86.6% performance variability attribution. Unexplored variables account for the remaining 13.4%.